PL201, a Reported Rhamnoside Against Alzheimer's Disease Pathology, Alleviates Neuroinflammation and Stimulates Nrf2 Signaling - An, Yuqian; Zhang, Hong; Huang, Shichao; Pei, Gang (Frontiers in Immunology, 2020)
Neuroinflammation induced by overactivated glia cells is believed to be a major hallmark of Alzheimer's disease (AD) and a hopeful target against AD. A rhamnoside PL201 was previously reported to promote neurogenesis and ameliorate AD, and in this study, we revealed that PL201 also significantly reduced accumulation of the activated microglia and proinflammatory cytokines in APP/PS1 mice. In vitro, PL201 consistently suppressed the microglia induction of proinflammatory cytokines after stimulation with lipopolysaccharides and Aβ42. Further mechanistic studies demonstrated that PL201 considerably enhanced the expression level and the nuclear translocation of Nrf2, a key regulator of neuroinflammation. Moreover, PL201 effectively stimulated Nrf2 signaling cascade, including upregulation of HO-1 and downregulation of NF-κB pathway. Thus, our findings indicated the anti-neuroinflammatory effect by PL201 in vivo and suggested that PL201 or the like, with multiple functions such as neurogenesis, mitochondria maintenance, and anti-neuroinflammation, could be a promising candidate in AD treatment.